SR ISOTOPES OF THE SEOGUIPO FORMATION (KOREA) AND THEIR APPLICATION TO GEOLOGIC AGE - Khim B.K.; Woo K.S.; Sohn Y.K. (My University, 2001)
The Seoguipo Formation, Cheju Island, Korea is a shallow-marine to nonmarine sedimentary formation formed by the earliest stage of volcanism and simultaneous volcanogenic sedimentation of the island. The formation contains signatures of glacioeustasy, providing an opportunity to study Neogene paleoceanographic changes in the northwestern Pacific. The proposed geologic age of the formation varies widely from Pliocene to Pleistocene in spite of an abundance of biostratigraphic and paleomagnetic data. This situation has hampered establishment of a time framework on which paleoenvironmental interpretations can be based. In this study, strontium isotopic ratios were measured from diverse macrofossils obtained from the fossiliferous lower part of the formation to constrain the carbonate ages. All macrofossils retain the original mineralogy and microstructures, negating the possibility of postdepositional diagenesis. The stable oxygen and carbon isotopic compositions of the specimens also show little sign of alteration. 87Sr/86Sr ratios of the shells display a wide range of values (0.70863-0.70919), categorized into two groups; calcitic pectenids, brachiopods, and an aragonitic bivalve showing high 87Sr/86Sr values (greater than 0.70909), and the rest of bivalves and an aragonitic gastropod showing unusually low values. The low 87Sr/86Sr ratios of the latter group are interpreted to be due to the local variation of the paleoseawater condition in which the organisms grew, probably caused by contemporaneous volcanic activities and weathering of volcaniclastic materials in a restricted environment. The average 87Sr/86Sr ratio of the heavy group yields a carbonate age of 0.86 (+0.40/-0.57)Ma by the LOWESS fit to the marine Sr-isotope curve of Howarth and McArthur (J. Geol., 105 (1997) 441). The Sr isotope age, in conjunction with radiometric and biostratigraphic ages, suggests that the deposition of the Seoguipo Formation began since the early Pleistocene, and the surface exposure of the formation belongs mostly to the middle Pleistocene (~0.86-0.4Ma).
Keywords: SEOGUIPO FORMATION; ISOTOPES; GEOLOGIC AGE; Neogene; Pleistocene; Pliocene; Cenozoic::Neogene; Cenozoic::Quaternary::Pleistocene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген; Кайнозой::Четвертичная::Плейстоцен; Кайнозой::Неоген::Плиоцен